(3JWhQ GdacQ GdGbJUGOj (B/s - (3GdbQjTj, eOMJs ((3YeGf(B: s (3OGQ hGFd ddfTQ h GdJhRjY(B, s, 2008)
(3JMOK Yf GdHOGjGJ GdYdejI ddacQ GdEbJUGOj h JWhQ eaghe Yde GdEbJUGO haGFOI OQGSI JWhQ GdacQ , h JfGhd GdacQ GdEbJUGOj GdZQHj aj GdYUhQ GdhSWi ,h bhGYO h bGOI GdacQ GdEbJUGOj GdESdGej aj GdYUhQ GdhSWi , h HYV GdeOGQS GdQCSeGdjI h GdcdGSjcjI h GdfjhcdGSjcjI ,h GdJegjO GdYdej ddEbJUGO GdSjGSjs
(3HjHdjhZQGajG U(B.327s
Keywords: (3GdGbJUGO GdeGdjs; (3GdacQ GdGbJUGOjs; (3GdfXQjGJ GbJUGOjIs; (3ePGgH GbJUGOjIs